Pengetahuan dan Sikap Kesehatan Prakonsepsi Calon Pengantin Wanita dalam Pendidikan Pranikah: Studi Quasi Eksperimental - Amizuar, Yulia Fauziah; Serudji, Joserizal; Oktova, Rafika; Semiarty, Rima; Karmia, Hudila Rifa; Rita, Rauza Sukma (jitek, 2024)
Maternal and child health challenges have been seen before the process of pregnancy. Improving education, attitudes and behavior of couples is an important part of preconception health. The aimed of this research was to verify the impact of premarital education on enhanced knowledge and attitudes of preconception health on brides. Research method was quasi-experimental, pretest-posttest control group design. Sampling technique was purposive sampling, based on inclusion and exclusion criteria. Time and location of the study September-November 2022 at three Office of religious (KUA Koto Tangah, KUA Kuranji and KUA Padang Utara). The intervention group were given educational material related to marriage law in Islam and preconception health education using lecture and discussion methods. The control group were given education only related to the law of marriage in Islam (religious sphere) with the lecture method. Questionnaires with tested validity and reliability were used to gather data. The results of knowledge intervention group compared the control group (p = 0.00). Prospective bride’s attitudes were not impacted by premarital education in the intervention group compare the control group (p=0.59). In conclusion, it has been proven that premarital education enhance preconception health knowledge, as opposed to women' preconception health attitudes.